GAMBARAN BRAND EXPERIENCE DAN BRAND LOVE IPHONE PADA KOMUNITAS FANSPAGE FACEBOOK IPHONE INDONESIA - Hanifah, Silvana; Rahayu, Agus; Dirgantari, Puspo Dewi (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to see the description of brand experience and brand love.Design / methodology / approach - The design of this study is cross sectional. This research uses descriptive approach with survey explanatory method as much as 83 respondents. A questionnaire was used as a research instrument to collect data from respondents. Analytical technique used is descriptive technique by using frequency table.Findings - Based on the results of the research using descriptive analysis, the result of the experience brand is in the high category with with a score of representative 94.18% and the love brand is in high category with with a score of representative 64.60%.Originality / value - This research provides is condusted on telecommunication industry with the object of research is a product from famous brand. The dimensions and indicators used to measure of variablethe are theories consumer-brand relationship.